The effect of acupuncture-related therapies in animal model of postmenopausal osteoporosis: a meta-analysis and data mining approach - Yu, Guangbin; Gao, YingYing; Song, Hongyuan; Chen, Guizhen; Xu, Yunxiang (Frontiers in Endocrinology, 2025)
PurposeThis meta-analysis and data mining aimed to investigate the effectiveness of Acupuncture-Related Therapies for animal models with Postmenopausal Osteoporosis (POMP) and to summarize the acupoints involved.MethodsThis systematic review was conducted a comprehensive search of animal experiments using acupuncture-related therapies for the treatment of PMOP up to April 1, 2025. The primary outcome was bone mineral density (BMD). The secondary outcome indicators were estradiol(E2), blood calcium, osteocalcin(OC) and alkaline phosphatas(ALP).Meta-analysis was used to evaluate its efficacy, and data mining was used to explore the protocol for acupoint selection.Results27 Animal Experiments encompassing 548 animals with PMOP were analyzed. Meta-analysis displayed that compared with the conventional drug group, the acupuncture-related therapy group significantly increased the Estradiol (mean difference [MD] 2.37,95% confidence interval [95%CI] 1.15 to 3.58), Femoral BMD (mean difference [MD] 1.25,95% confidence interval [95%CI] 0.65 to 1.87), lumbar BMD (mean difference [MD] 1.88,95% confidence interval [95%CI] 1.27 to 2.49), Tibia BMD (mean difference [MD] 1.63,95% confidence interval [95%CI] 0.56 to 2.69). Data mining revealed that Zusanli (ST36), Shenshu (BL23), Guanyuan (CV4), and Sanyinjiao (SP6) were the core acupoints for PMOP treated by Acupuncture-Related Therapies.ConclusionAcupuncture improved BMD and estrogen levels in animal models of PMOP. ST36, BL23, CV4, and SP6 are the core acupoints for acupuncture in PMOP, and this program is expected to become a supplementary treatment for PMOP.